KOEFISIEN LIMPASAN PERMUKAAN PADA PERKERASAN PAVING BLOCK BERPORI - YASA, I WAYAN; SUPRIYADI, ANID; PRAJNA D, KADEK AGUS (Universitas Mahasaraswati Mataram, 2020)
The use of pavement is increasing, especially in urban areas. Various types of pavement are used including asphalt, concrete and paving blocks. The use of pavements tightens the filtration and increases the volume of surface runoff. One of the pavements used to reduce runoff is paving blocks. The open area between paving blocks is the most influential factor in increasing water infiltration in paving blocks. The larger the opening area in the paving, the more water absorption capacity will be.This research uses infall simulator to model rain. The pavement used is a square porous paving block with a size of 20 x 10 x 8 cm. Variations in the number of pores are 3 holes, 5 holes and 9 holes. The area comparisons between paving blocks and pore holes were 99.4% and 0.6%, 99% and 1%, 98.2% and 1.8%, respectively. Measurements taken are the measurement of rain intensity, runoff volume, infiltration volume and surface break-even coefficient (C).The results showed that the addition of pore holes had an effect on the surface runoff coefficient. In square paving blocks without pores, the coefficient value is greater. Poreless square paving blocks have the highest runoff coefficient with values ranging from 0.41 to 0.45, square paving blocks with 3 porico holes, runoff efficiency ranges from 0.39 to 0.43, paving blocks with 5 pore runoff coefficients range from 0.38 - 0.42, and a square paving block with 9 pore holes, the smallest runoff coefficient ranges from 0.37 to 0.41.